USAHA PENINGKATAN PERFORMANSI MOTOR DAN ANALISIS KEGAGALAN SPAREPART RACING PADA PROSES PERAKITAN MENGGUNAKAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Sinaga, Zulkani; Muhajir, Achmad; Hael G, M. Habib (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
STR Workshop is a company engaged in the automotive manufacturing sector. The production activities involve modifying motorcycle engines to enhance their performance using racing spare parts. However, during the production process, failures were encountered with the components themselves. Therefore, it is necessary to conduct research to assess the extent of damage to the engine using the FMEA (Failure Mode and Effects Analysis) method. Based on the research findings, there are four types of component failures in the engine, including broken valve springs, hollow pistons, broken valve springs, and cracked liner bores. Using the FMEA method, several factors were identified, resulting in a Severity rating of 7, Occurrence rating of 6, and Detection rating of 3, leading to a Risk Priority Number (RPN) of 126 for the piston. This indicates that the engine modification experienced failures during the assembly process.Furthermore, the measurement of motorcycle engine performance using a dynamometer showed that after modifications were made to the Vario 150 cc motorcycle—where the standard piston diameter increased from 57.3 mm to 60 mm, and the compression ratio changed from 10.6:1 to 11.3:1—the horsepower increased from 9.7 at 8500 RPM to 19.0 at 11000 RPM.Keywords: Performance, Defect, Motorcycle Engine, FMEA